Hyperhydration in Burn Patients: the Current State of the Issue - T. G. Spiridonova; E. A. Zhirkova; I. G. Borisov (Неотложная медицинская помощь)
The article presents the current state of hyperhydration issue in burn patients as a result of excess volume of infusion therapy during the acute period of burn disease. We report the data on the pathogenesis of burn disease and standard formulas for determining the volume of infusion therapy in case of burn shock, mechanisms and clinical manifestations of hyperhydration in burn patients and modern methods of its management. Since the danger of hyperhydration persists even after a shock in an acute period of burn disease, a method is proposed for determining the baseline volume of infusion therapy in the post-shock period. The developed algorithm is effective for prevention of hyperhydration in burn patients and covered by an invention patent.